Preferensi Digitalisasi dan Literasi Pajak dalam Meningkatkan Kepatuhan Pajak Penghasilan Generasi Muda di KPP Pratama Majalaya - Eris Kusmawati; Maharani Rahma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The younger generation born in the digital age has great potential to support tax collection. However, the low level of tax compliance among the younger generation is a major concern, especially in the digital age, where the use of online tax services is not yet optimal, tax literacy is still limited, and a lack of socialization is an obstacle to utilizing digital services. This study aims to analyze the influence of preferences for digital tax services and tax literacy on tax compliance among the younger generation at the Majalaya Tax Office. The study uses a quantitative approach with surveys as the data collection method. The sample consists of young taxpayers registered at the Majalaya Tax Office, and the data is analyzed using linear regression to test the partial and simultaneous effects of independent variables on tax compliance. The results show that digitalization preferences have a positive and significant effect on tax compliance, indicating that younger generations who are more responsive to digital services tend to be more compliant. Tax literacy also has a positive and significant effect, showing that a sufficient understanding of tax rights, obligations, and regulations encourages compliance. Simultaneously, the combination of digitalization preferences and tax literacy significantly affects tax compliance, with a coefficient of determination of 0.438, meaning that 43.8% of the variation in compliance can be explained by these two variables. The findings of this study emphasize the importance of integrating easy access to digital services and improved tax literacy to encourage tax compliance among the younger generation.